1997
DOI: 10.1177/0011128797043004009
|View full text |Cite
|
Sign up to set email alerts
|

The Transfer of Juveniles to Criminal Court: Reexamining Recidivism Over the Long Term

Abstract: A long-term recidivism study was conducted in Florida on matched pairs of juveniles, where one subject in each pair had been transferred to the adult system in 1987 and the other had not. Rearrest information on the pairs from their release from sanctions through November 1994 was used to determine the probabilities of rearrest and the times to rearrest of transfers and nontransfers, adjusting for time at risk. Transfer diminished the rearrest chances for property felons, an advantage that was offset by an enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 8 publications
4
97
0
1
Order By: Relevance
“…These findings are consistent with those of Bishop and Frazier (2000), whose interviews with juveniles in the criminal justice system reveal the anger and resentment they feel about being tried and sentenced as adults. It has been suggested that juveniles' sense of injustice at criminal court processing may cause them to react defiantly through re-offending and only harden their concept of themselves as "criminals" (see Matza, 1964;Thomas & Bishop, 1984;Winner, Lanza-Kaduce, Bishop, & Frazier, 1997). "The concept of fairness appears to be an important variable in an individual's perception of sentence severity and its subsequent relationship to future recidivism" (Corrado et al, 2003, p. 183;see Morris & Giller, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with those of Bishop and Frazier (2000), whose interviews with juveniles in the criminal justice system reveal the anger and resentment they feel about being tried and sentenced as adults. It has been suggested that juveniles' sense of injustice at criminal court processing may cause them to react defiantly through re-offending and only harden their concept of themselves as "criminals" (see Matza, 1964;Thomas & Bishop, 1984;Winner, Lanza-Kaduce, Bishop, & Frazier, 1997). "The concept of fairness appears to be an important variable in an individual's perception of sentence severity and its subsequent relationship to future recidivism" (Corrado et al, 2003, p. 183;see Morris & Giller, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Although transfer laws continue to receive a fair degree of public support (Brannen et al, 2006), they have also drawn substantial criticism. In particular, there is a sizeable body of research evidence indicating that transferred juveniles are more likely to recidivate than youth who are retained in juvenile court even after a number of risk-related variables (e.g., number of past offences) are controlled for (Bishop et al, 1996;Fagan, 1996;Fagan et al, 2003;Lanza-Kaduce et al, 2005;Winner et al, 1997). This research suggests that the transfer process itself may have iatrogenic effects (e.g., Redding, 2008).…”
Section: List Of Tablesmentioning
confidence: 99%
“…Bishop and colleagues have published several studies comparing the recidivism rates of juveniles who are transferred to the adult system with those who are not (Bishop et al 1996;Winner et al 1997). In one study (Bishop et al 1996), they match transferred and nontransferred juveniles on observable covariates (for example, number of prior offenses, offense seriousness, sex, race, and age).…”
Section: Prior Literaturementioning
confidence: 99%